(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
In today’s digital age and in light of the modern developments directed by the world, education plays a pivotal role in promoting the values ​​​​that promote sustainable development. The study aimed to study the impact of mutual education and factors of sustainable economic growth during the period (1997-2023) using the Least Squares method and adopting the software (Eviews10). The research reached several results, including that the effect of the variable of total public spending on education is significant but negative on economic growth. Because that The state of Finland has reached high subscription services even if it has achieved education without increasing spending on education, so the lowest average level in public spending is providing services or direct financing services from starting children and their subjects, which is much higher than modifying and improving work functions can improve the type Services, education, and their comprehensive care, when appropriate conditions are available for this, will affect their control and good job satisfaction.